DESCRIPTION OF HISTOPATOLOGICAL FEMORAL FRACTURES HEALING WITH EXCESSIVE OF CALCIUM-CARBONATE TREATMENT IN MALE RAT - Sari Yudaniayanti, Ira; -, Hartiningsih; Budi Santoso, Agus (Jurnal Veteriner, 2008)
Fracture healing is a complex process that requires the ordered synthesis of matrix proteins and deposition of mineral. Complications such as delayed union or non-union may arise from excessive flexibility bone because low mineral content of bone or apposition of both fracture fragments is not complete yet. The aim of this study is to determine the effect of excessive calcium carbonate (CaCO3) on the healing femoral fracture in rat by examining histopathological change of femoral fracture. Twelve male Sprague Dawley rats, 12 weeks old were subjected to this investigation. The entire rats model at 13 weeks old were treated reposition of femoral dexter fractures with intramedullary pin fixation. The rats model were evenly randomly divided into three groups of four at 15 weeks old ; group I treated with normal diet, group II with normal diet + CaCO3 supplement 75 mg/day, group III with normal diet + CaCO3 supplement 225 mg/day per oral. At the end of the experiment (19 weeks old), the rats were killed, subsequently dexter femur were taken out for determining the histopathological examination. The results showed that excessive suplementation CaCO3 to description of histopathological fracture healing on group III had even better, callus was able to bridge the fracture fragment with completely. The proportion woven bone and trabeculae were higher, while group II were cartilage dominate in callus, and group I were higher fibrous tissue. From the results can be concluded that given CaCO3 225 mg/ day accelerate the healing process of femoral fractures.
Keywords: CaCO3, , histopathology, woven bone, bone trabeculae and bone fibrous tissue